Power Loss Reduction and Reliability Improvement of Radial Distribution Systems Using Optimal Capacitor Placement Technique - Mohanad Muneer Yaqoob; Ali Nasser Hussain; Wathiq Rafa Abed; Daniel Augusto Pereira (Journal of Techniques)
Improving reliability and power quality in Radial Distribution Systems (RDS) is of large significance to ensure the provision of electricity within a reliable and acceptable standard to consumers with increasing load requirements. An Optimal Capacitor Placement (OCP) technique is used in the present work to achieve the highest power quality and system reliability in a balanced manner at the same time. The proposed technique has been tested with 69 typical IEEE RDS buses using the Improved Binary Particle Swarm Optimization (IBPSO) algorithm. The proposed algorithm shows a high ability to find the best location and size of injected capacitors inside the RDS to implement a single-objective function for minimization of Active Power Loss (APL). The simulation results obtained from the MATLAB environment show that the OCP technique has a significant potential to enhance RDS reliability, bus voltage, and loss reduction as compared to other previous work.